Antibodies and Tyrosine Kinase Inhibitors in Breast Cancer Therapies - Barth, J. (S. Karger GmbH, 2009)
In recent years, new classes of molecules have been established as opportunities for the treatment of breast cancer. The approval of trastuzumab, the antibody against Her2/neu, in the late 1990s was followed by the approval of the antiangiogenic antibody bevacizumab in 2007. Progress in the understanding of the molecular mechanisms of carcinogenesis and tumour growth led to the development of new molecules, mostly kinase inhibitors. A few of these new molecues gained approval in several countries; clinical trials aiming at further approvals are ongoing. This short review covers the actual state-of-the-art and possible future developments in the targeted therapy of breast cancer.